An annotated bibliography of theses submitted by MBA/MBM graduates of selected institutions in Metro Manila, 1965-1975 - Manago, Emiliana M. (1979)
This special problem aims to provide businessmen, business consultants, students of business and economics, librarians, teachers and other engaged in research and business operation with an annotated bibliography of theses completed by MBA/MBM graduates from seven institutions in Metro Manila during the academic year 1965 through 1975.